The Italian language postpartum specific anxiety scale [PSAS-IT]: translation, psychometric evaluation, and validation - Ionio, Chiara; Ciuffo, Giulia; Landoni, Marta; Smorti, Martina; Della Vedova, Anna Maria; Christiansen, Paul; Fallon, Victoria; Silverio, Sergio A.; Bramante, Alessandra (Frontiers in Psychiatry, 2023)
Introduction: Whilst often positive, the lifecourse transition to motherhood is susceptible to the risk for developing mood disorders. Postpartum anxiety has often been overshadowed by other perinatal-specific mental health disorders, such as postpartum depression, and therefore has not been at the forefront or centre of as much empirical study. This has meant there is a lack of effective and reliable tools with which to measure it, despite growing evidence suggesting its detrimental impact on mothers, their babies, wider family and social contacts, and on healthcare systems. This current study aimed to translate and validate the Postpartum Specific Anxiety Scale [PSAS] into the Italian language, and to validate the tool for its use in detecting anxiety specific to motherhood. Methods: The study (N=457) comprised 4 stages: English-Italian translation and back-translation to obtain the Italian version [PSAS-IT]; a preliminary pilot study to adapt the PSAS to the characteristics of the Italian population; measurement invariance; and internal reliability of subscales. Results: The PSAS-IT demonstrates similar psychometric properties as the original English-language PSAS, with acceptable acceptability, construct and convergent validity, and internal consistency. Confirmatory factor analysis for multiple groups (Italy and United Kingdom) showed that the factor structure of the PSAS was valid for both groups (χ2 (2436) = 4679.481, p<.001, TLI= 0.969, CFI =.972, RMSEA=0.045, SRMR =0.064). Discussion: The resulting findings offer a reliable measure of postpartum anxiety in Italian language up to six months after birth.